Virtual acoustics: opportunities and limits of spatial sound reproduction - VORLAENDER, Michael (Archives of Acoustics, 2008)
Virtual Acoustics is part of the emerging field of "Virtual Reality". The technology for creating a Virtual Reality, VR, for wide variety of applications in university and industry has been developed in the last decade. Mostly VR is understood as a tool for 3D visualization, rather than for spatial audio or room acoustics. Nevertheless an important requirement of VR is the multimodal approach which includes vision, sound, tactile and haptic stimuli. The process of creating a physical stimulus based on computer data is called "rendering". The development of rendering and reproduction of acoustic stimuli in VR is now at a stage where integration of 3D sound is feasible by using PCs. This applies to multi-channel binaural synthesis as well as to full room-acoustic simulation algorithms and to various applications of 3D sound stimuli for audiology, neuropsychology or any other application in acoustics and noise control.